Assessment of diverse resources of ground water quality in Budaun district (U.P.), India - Deepa Singh (G-Journal of Environmental Science and Technology, 2013)
Ground water is one of most important source of the domestic water use. The water supply bodies’ i.e. Municipal Corporation Jal nigam, or Nagar nigam are mainly depends on the ground water resources of the area. In the light of all these facts the work was demonstrate in the Budaun city to access the current ground water quality of the city. The minimum to maximum temperature value was observed 20.4oC to 21.6 oC while pH value ranged between 7.0 to 7.5. The minimum to maximum Turbidity value was observed 4.1 to 4.6 NTU. The minimum to maximum Dissolve Oxygen value was observed 4.0 to 4.9mg/lit. The minimum to maximum TDS value was observed 335 to 369 mg/l. The minimum and maximum Total Hardness value was observed 119 and 135 mg/l. The minimum to maximum Calcium Hardness value was observed 64 to 75 mg/l. The minimum to maximum Magnesium Hardness value was observed 24 to 30 mg/l. The result comes out of study shows that the ground water is fit for consumption.